Analysis of Factors Affecting the Success of Pulmonary TB Treatment at the North Sumatra Specialized Lung Hospital 2020–2023 - Syahrida Syahrida Hasibuan; Zuhrina Aidha (PROMOTOR, 2026)
Indonesia is the country with the second highest TB burden in the world, but the treatment success rate is still below the 2020-2024 Strategic Plan target of ≥90%. Incomplete treatment increases the risk of multidrug-resistant tuberculosis (MDR-TB), which is difficult and expensive to treat, thereby worsening Indonesia's health system. This study aims to analyze the factors that influence the success of pulmonary tuberculosis (TB) treatment at the Provincial Specialized Pulmonary Hospital (UPTD RS Khusus Paru Pemprovsu) during the period 2020–2023. Using a case-control design with a retrospective observational analytical approach and simple random sampling (SRS) technique, this study involved 266 respondents, consisting of 133 cases and 133 controls. Data analysis was performed using univariate, bivariate (chi-square test), and multivariate (binary logistic regression) methods. The results showed that age, gender, employment status, comorbidity status, and treatment regimen type were significantly associated with TB treatment success. The treatment regimen type factor had the most significant influence, with patients in regimen category 1 having an almost seven times greater chance of recovery (OR 6.857, p-value 0.001).